Organizing the good death: ethics and values-work in the Sower Hospice - Rio, María Dolores del (Journal of business ethics, 2025)
We study the relationship between values-work and virtue ethics in organizations. Drawing from an ethnographic study of a hospice for the poor in Buenos Aires, Argentina, we demonstrate how organizational practices of values-work are used to combat the disenchantment of modern medical treatment of death. We identify three core sets of practices, Humility, Sympathetic Impartiality, and Practical Wisdom, each premised on humanistic virtues used to counteract the totalizing pressures of rationalization and professionalization of modern medicine. We theorize how the Sower Method of organizing a "good death" might be applied to counteract the disenchanting effects of organizing contemporary work.